The Criminal Acts of Perpetrators for Threats on the Social Media - Perwitasari, Dinda Tri Novia; Hapsari, Ifahda Pratama (Universitas Islam Sultan Agung, 2024)
This study aims to learn more about the criminal provisions applied and identify the nature of the criminal consequences for perpetrators of threats in Indonesia, especially on social media by considering the elements of criminal acts and legal subjects. The writing method uses normative legal techniques. To resolve legal disputes, conceptual and legislative frameworks are used. The novelty of this research lies in the discussion of a broader scope, namely regarding the basis for criminal responsibility of perpetrators of threats and elements of criminal acts for perpetrators of threats in Indonesia. Based on the research concluded It is proven from the results that an act of threat and insult on social media can be subject to the articles regulated by Law No. 19 of 2016 (Articles 29 and 45B) concerning ITE has provided sanctions in accordance with a criminal penalty of no more than four (4) years in prison or a fine of 7,500,000 rupiah (Rp). On the other hand, when it comes to finding out how those who insult or threaten others in Indonesia may face criminal charges, it is not only seen from the elements but it is important to see it from the perspective of the legal subject. So that perpetrators who meet the requirements for criminal responsibility for threats on social media are required to be responsible for their actions before the law.